Associations between long working hours, leisure-time physical activity, and work-related musculoskeletal disorders among multi-industry workers in Nanchong - Jing QIU; Hairong WANG; Wei ZHOU (环境与职业医学)
BackgroundWork-related musculoskeletal disorders (WMSDs) are considered to be one of the biggest health problems in the workplace, seriously affecting the productivity and quality of life of the working population. Long working hours may associate with WMSDs, and leisure-time physical activity (LTPA) is beneficial for WMSDs. However, the independent and combined effects of these two factors on WMSDs remain poorly understood. ObjectiveTo explore the independent and joint relationships between long working hours, leisure time physical activity (LTPA), and WMSDs, and to provide a basis for prevention and intervention of WMSDs. MethodsA cross-sectional survey was conducted among 1227 frontline workers from multiple secondary industry companies in Nanchong City in 2023 using cluster random sampling. Demographic characteristics information, weekly working hours, LTPA, personal health behaviors, and occupational factors were collected through questionnaires. The Chinese version of Musculoskeletal Disorders Questionnaire was used to assess WMSDs. χ2 test and logistic regression were used to analyze the relationships between long working hours and/or LTPA and WMSDs. ResultsA total of 1227 workers were surveyed with a mean age of (41.3±9.3) years and 855 (69.7%) were male and 372 (30.3%) were female. Among then, 855 (69.7%) workers reported working >40 h per week, and 254 (20.7%) reported working ≥ 55 h per week; 561 (45.7%) reported no LTPA and 192 (15.6%) reported high LTPA. The overall positive rate of WMSDs was 57.4%. The positive rate of WMSDs was 71.3% in those working ≥55 h per week, which was significantly higher than those in the other groups (51.3%-58.2%, P<0.05). Comparison among the positive rate of WMSDs in the weekly working 41-48 h group (54.4%), the 49-54 h group (58.2%), and the ≤40 h group (51.3%) showed no statistically significant difference (P>0.05). The positive rate of WMSDs was higher in workers with no LTPA (59.0%)/low LTPA (58.9%) than in those with high LTPA (49.0%) (P<0.05). The logistic regression models showed that after adjusting gender, age, work experience, income per month, night shift, industry, prolonged fixed posture, prolonged repetition, smoking and alcohol drinking, compared with weekly working ≤40 h, the risk of WMSDs was higher in those with extra-long working hours (≥55 h·week−1 ) (OR=2.155, 95%CI: 1.504, 3.088), whereas those with high LTPA had a lower risk of WMSDs (OR=0.614, 95% CI: 0.432, 0.874 ). The combination of no LTPA and extra-long working hours (≥55 h·week−1) and low LTPA and extra-long working hours (≥55 h·week−1) showed associations with WMSDs, with 2.360 and 2.049 times higher risk of WMSDs than that of the combination of no LTPA and standard working hours (≤40 h ·week−1) respectively (P<0.05), whereas the combination of high LTPA and long working hours was not observed statistical significance (P>0.05). ConclusionExtra-long working hours and/or LTPA show different associations with the risk of WMSDs. Extra-long working hours are significantly positively associated with the risk of WMSDs, whereas high LTPA is significantly negatively associated with the risk of WMSDs. The combination of extra-long working hours with no or low LTPA is associated with elevated risk of reporting WMSDs, whereas no statistical significance is observed for the high LTPA-long work hours combination.